1996
DOI: 10.1101/gr.6.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and evolution of CTG repeats at the myotonin protein kinase gene in human populations.

Abstract: We have analyzed the CTG repeat length and the neighboring A/u insertion/deletion [+/-) polymorphism in DNA samples from 16 ethnically and geographically diverse human populations to understand the evolutionary dynamics of the myotonic dystrophy-associated CTG repeat. Our results show that the CTG repeat length is variable in human populations. Although the (CTG}5 repeat is the most common allele in the majority of populations, this allele is absent among Costa Ricans and New Guinea highlanders. We have detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 25 publications
7
35
1
Order By: Relevance
“…The most frequent allele was different between Caucasians and Asians: five repeats is the most common in European, and 12 repeats in Japanese [7,8]. In Koreans, a previous study reported the range of CTG repeats to be 5 to 34, and (CTG)11-14 as the predominant alleles [9].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent allele was different between Caucasians and Asians: five repeats is the most common in European, and 12 repeats in Japanese [7,8]. In Koreans, a previous study reported the range of CTG repeats to be 5 to 34, and (CTG)11-14 as the predominant alleles [9].…”
Section: Discussionmentioning
confidence: 99%
“…These data include allele frequencies at 116 dinucleotide loci (details available on request), 3 neutral trinucleotide loci (D19S190, D19S261, and SCN1B), 1 disease trinucleotide locus (DM), and 12 tetranucleotide loci (D19S244-D19S47, D19S250-D19S255, and EPOR). Table 1 shows the summary results of the ANOVA of the natural logarithms of locus-and population-specific variances of allele sizes (lnV ijk ) for the first two sets of data (16)(17)(18)(19)(20). For both sets of data, the component of variation due to population differences is not significant (P Ͼ 0.75)-i.e., x j ϭ lnN j is nearly constant over all j in both sets of data.…”
Section: Datamentioning
confidence: 99%
“…The first set is described in refs. [16][17][18]. It includes allele frequencies at eight dinucleotide (FLT1, D13S118, D13S121, D13S71, D13S122, D13S197, D13S193, and D13S124), five trinucleotide (PLA2A, DM, SCA, DRPLA, and HD), and five tetranucleotide (THO1, CSF1R, F13A1, CYP19, and LPL) repeat loci in samples from nine populations (unrelated Caucasians from the Centre d'É tude du Polymorphisme Humain panel; Germans; Brazilian Whites; Brahmins from Uttar Pradesh, India; Sokoto from Nigeria; Benin; Brazilian Blacks; Japanese; and Chinese).…”
Section: Datamentioning
confidence: 99%
“…Analysis of the DMPK alleles of these individuals showed a tri-modal distribution of (CTG) n repeat size similar to that previously observed in other populations of predominantly European ancestry (Figure 1). 21,26,27 The sample was found to be in HardyWeinberg equilibrium (P ¼ 0.4). This suggests that although our study group was a selected group that had difficulty to conceive, it was not different from the general population with respect to the distribution of the DMPK alleles.…”
Section: Resultsmentioning
confidence: 99%
“…However, the distribution of the DMPK alleles within our study, which was not selected for ethnicity, but was largely French Canadian, showed a similar tri-modal pattern and prevalence of (CTG) 5 repeats as previously observed in other populations of predominantly European ancestry (Figure 1). 21,26,27 If infertility were associated with a change in transmission patterns, one would expect this to be reflected in the distribution of allele frequencies.…”
Section: Discussionmentioning
confidence: 99%